Investigation of potent odorants and afterodor development in two Chardonnay wines using the buccal odor screening system (BOSS) - Büttner, Andrea (Journal of Agricultural and Food Chemistry, 2004)
Potent odorants of two Chardonnay wines were characterized according to their specific overall aroma profiles and their intraoral release patterns after wine consumption. Therefore, aroma compounds were isolated and analyzed by means of high resolution gas chromatography-olfactometry (HRGC/ O), leading to the detection of 36 odor-active compounds in both wines. All compounds were identified. Of the most potent odorants, 25 were quantified in both wines by means of stable isotope dilution assays. For the intraoral investigation of odor compounds at defined times after Chardonnay wine consumption, the recently developed buccal odor screening system was used. Significant differences in the oral persistence of characteristic odor notes were observed for both wines with mainly the characteristic barrique-notes being highly persistent, while fruity notes quickly disappeared from the oral cavity. The obtained analytical data were related to time-resolved retronasal aroma evaluation.
Keywords: aftersmell; stir bar sorptive extraction; aroma persistence; finish